Treatment of subchondral cystic lesions (SCLs) with parathyroid hormone peptide (PTH1‐34)‐enriched fibrin hydrogel in three different concentrations: A dose‐blinded, randomised study. (21st November 2018) - Jackson, M. A.; Ohlerth, S.; Brink, P.; Simon, O.; Kummer, M.; Fürst, A. E.
Summary: This study reports the use of parathyroid hormone fragment peptide 1‐34 (PTH1‐34 ) cross‐linked to a hydrogel in a fibrin base for the treatment of subchondral cyst‐like lesions (SCLs). The objectives were to determine the clinical and radiographic outcome of 28 horses with lameness attributable to one or two SCLs treated locally with one of three different concentrations of PTH1‐34 and to identify which concentration produces the best results. Twenty‐eight horses (34 SCLs) were treated surgically by debriding the content of the SCL and injecting different concentrations (0.1, 0.4, or 1 mg/mL) of PTH1‐34 in a fibrin hydrogel into the cavity. Treatment was considered successful if the horse was sound 12 months after treatment. The mean age of the horses was 7.2 years. Treatment was successful in 22 (78.6%) horses and improved the radiographic appearance of 27 (79.4%) SCLs. The outcome was not affected by age of the horse or by the number of SCLs (1 or 2) per horse. PTH1‐34 in a fibrin hydrogel administered into the SCL after surgical debridement of the lesion appears to be an effective treatment for horses with one or two SCLs. A PTH1‐34 concentration of 0.4 mg/mL may be slightly superior to concentrations of 0.1 and 1.0 mg/mL in resolving SCLs.